Sexually dimorphic muscle development - Hanafi Sulong
Sexually dimorphism in chickens can be distinguished clearly during the post-hatch period where in male chicken is significantly bigger and heavier than female chicken. The differences in sexual phenotype were previously assumed to be the result of different sex hormone action in male and female birds until recently studies indicated that avian somatic cells possesses inherent sex identity of male and females known as cell autonomous sex identity (CASI). The studies on gynandromorph birds (a rare and naturally occurring phenomenon) showed that one side of the chicken appears male and the other side as females. Further studies were done on a sex-determining mechanism in this birds revealed that gynandromorph birds are genuine male: female chimeras. This suggests that sex identity is cell autonomous as male and female phenotypes arise from the same gonadal hormones profile and rules out the action of a sex-determining master gene. Therefore, to increase the understanding of the role of inherent sex identity that will influence the somatic cell development, a study on breast muscle development of male and female embryonic chicken was conducted. The objectives of the study were to compare the mass of male and female bird muscle as well as comparing the myofiber number and size of embryos at EI2.S. There were no sex differences in the body weight of embryos of the selected stages. However, surprisingly, there was a difference in the breast muscle weight at EI2.S. These differences lead to the in ovo injection of an aromatase inhibitor, Fadrazole to investigate the effects of sex reversal on muscle development. This paper proves that the male and female sex differences are not dependent on embryonic gonadal hormones.